Pengelolaan Platform Digital Penyiaran pada Urban Radio 106.3 FM - Astri Dwi Utari; Nova Yuliati (UNISBA Press, 2024)
Abstract. Urban Radio 106.3 FM is one of the modern radio stations broadcasting on the frequency 106.3 FM in the city of Bandung. This research is focused on the